18α-Glycyrrhetinic acid monoglucuronide as an anti-inflammatory agent through suppression of the NF-κB and MAPK signaling pathway12. Issue 7 (16th June 2017) - Li, Bo; Yang, Yongan; Chen, Liuzeng; Chen, Shichao; Zhang, Jing; Tang, Wenjian
Abstract : 18α-GAMG exhibited strong anti-inflammatory activity through inhibiting the expression of iNOS, COX-2, and MAPKs, as well as activation of NF-κB. Abstract : Based on the SAR analysis of glycyrrhizin, 18α-glycyrrhetinic acid monoglucuronide (18α-GAMG) with strong inhibition against LPS-induced NO and IL-6 production in RAW264.7 cells was discovered. Western blotting and immunofluorescence results showed that 18α-GAMG reduced the expression of iNOS, COX-2, and MAPKs, as well as activation of NF-κB in the LPS-stimulated RAW264.7 cells. Further in vivo results showed that 18α-GAMG could significantly improve the pathological changes of CCl4 -induced hepatic fibrosis.